2002
DOI: 10.1073/pnas.232580599
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the macrolide antibiotic tylosin is conferred by single methylations at 23S rRNA nucleotides G748 and A2058 acting in synergy

Abstract: The macrolide antibiotic tylosin has been used extensively in veterinary medicine and exerts potent antimicrobial activity against Gram-positive bacteria. Tylosin-synthesizing strains of the Gram-positive bacterium Streptomyces fradiae protect themselves from their own product by differential expression of four resistance determinants, tlrA, tlrB, tlrC, and tlrD. The tlrB and tlrD genes encode methyltransferases that add single methyl groups at 23S rRNA nucleotides G748 and A2058, respectively. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 55 publications
3
102
1
Order By: Relevance
“…Meanwhile, it has been reported that positions G748, A751 and A752 located within the loop of helix 35 of domain II are involved in tylosin-23S rRNA interactions in Gram-positive microorganisms (Hansen et al, 2002;Liu & Douthwaite, 2002a;Poehlsgaard & Douthwaite, 2005). Similarly, the role of position G745 in the tylosin-ribosome interactions in E. coli has been described (Liu & Douthwaite, 2002b), while positions G748 and A752 are reportedly involved in the interactions between ketolides and ribosomes (Novotny et al, 2004).…”
Section: Mechanism Of Actionmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, it has been reported that positions G748, A751 and A752 located within the loop of helix 35 of domain II are involved in tylosin-23S rRNA interactions in Gram-positive microorganisms (Hansen et al, 2002;Liu & Douthwaite, 2002a;Poehlsgaard & Douthwaite, 2005). Similarly, the role of position G745 in the tylosin-ribosome interactions in E. coli has been described (Liu & Douthwaite, 2002b), while positions G748 and A752 are reportedly involved in the interactions between ketolides and ribosomes (Novotny et al, 2004).…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…In the case of tylosin, the methylation at position A2058 does not by itself result in the development of resistance, but rather the concomitant methylation of other 23S rRNA positions, such as G745 or G748 in Gram-negative and Gram-positive microorganisms, respectively is needed (Liu & Douthwaite, 2002a, b). Thus, among others, Erm(32) (formerly TlrB or RlmA II ) encoded in the chromosome of members of the Streptomyces genus has been described to be able to methylate position G748 (Liu & Douthwaite, 2002a). In E. coli the presence of a related methylase, called RlmA I (formerly RrmA) has been described which acts by methylating position G745 (Liu & Douthwaite, 2002b).…”
Section: Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…4B) nor disrupt base pairing with U2528, suggesting that methylation at this position indirectly confers resistance by inducing local conformational changes, possibly during ribosome assembly. We note that both AviRa and AviRb are required to obtain full protection against the AVI (31), suggesting that they function in a synergistic manner, similar to the methyltransferases that cause resistance to tylosin (32). The EVN methyltransferase EmtA, which was identified on a plasmid-borne insertion element in EVN-resistant E. faecium strains (isolated from animals given AVI as a growth promotant), was shown to methylate G2470 of H89 (13).…”
Section: H89 H89mentioning
confidence: 99%
“…Most of these compounds inhibit cell growth by interfering with peptide bond formation (15). The second major antibiotic binding site in the large ribosomal subunit is located at the upper segment of the nascent peptide exit tunnel (NPET), adjacent to the PTC, and is used by macrolides and type B streptogramins (3,7,(16)(17)(18)(19)(20)(21). Binding to this site impedes progression of the nascent proteins toward the tunnel exit.…”
mentioning
confidence: 99%